Proces adaptacji rodziców do roli rodzicielskiej dziecka z zespołem Downa jako strategia radzenia sobie z sytuacją stresową - Kaliszewska, Karolina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The process of adaptation to the role of a parent of a child with Down Syndrome is very difficult, multi-staged and stress-causing both for mothers and for fathers. Coping with the parental stress is a constant challenge for mothers and fathers of a child with Down syndrome and it increases the significance of different types of social support. The choice of coping strategy influences parents’ cognitive abilities, competences of emotional and behavioural regulation and facilities more positive assessment of their intellectually disabled child. In case parents choose more adaptive, that is problem – focused coping strategy the adjustment to parental role proceed more fluent, or even more adequate. In addition, it has been proven that receiving social support and using accommodative coping style may boost the process of adaptation to parental role of a child with Down syndrome.